IMPLEMENTASI REVITALISASI PASAR GADING KOTA SURAKARTA - Wahyu Bhudianto, Annisa Miftahul Ulum, Joko Pramono & (Transformasi, 2015)
Judging from the indicators used to determine the implementation of the revitalization ofIvory Markets of Surakarta, communication is done by implementing policies in promotingpolicies that have been made to the target group. Factors resource that includes humanresources (HR), budget, facilities, and information and authority. Disposition, behavioraltendency executive officers in carrying out their responsibilities. Bureaucratic structure thatincludes two things: the mechanism and structure of the bureaucracy itself. Indicators toassess the success of the implementation of the market that has been done by implementingpolicies which starts from the delivery of the policy pursued by way of policy disseminationand then continued with the process of revitalizing itself and manufacturing SOPs that serveas guidelines for officers in providing services to those users who have adapted to the marketSurakarta ivory market vision has been implemented properly so that it can be said thatpolicy implementation has been carried out successfully.Conclusion The purpose of the revitalization of the market that is changing the negativeimage of traditional markets to improve the competitiveness of traditional markets in the eyesof the public in accordance with the vision that has been set.Key Word: implementation, revitalization of the market.